2021
DOI: 10.1097/sla.0000000000005228
|View full text |Cite
|
Sign up to set email alerts
|

Oncological Safety and Potential Cost Savings of Routine vs Selective Histopathological Examination After Appendectomy

Abstract: To investigate the oncological safety and potential cost savings of selective histopathological examination after appendectomy. Background: The necessity of routine histopathological examination after appendectomy has been questioned, but prospective studies investigating the safety of a selective policy are lacking.Methods: In this multicenter, prospective, cross-sectional study, inspection and palpation of the (meso)appendix was performed by the surgeon in patients with suspected appendicitis. The surgeon's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…A recent audit from the UK reported that more than 100 appendiceal specimens were not reviewed by surgeons, with no significant health or medico-legal implications after the operation [ 21 ]. A multicentric prospective analysis conducted in the Netherlands [ 16 ] involving 7,339 patients, included thorough inspection and palpation of the appendix and mesoappendix by surgeons. They found that 67.7% of the specimens would have been deemed unnecessary for histopathological examination, as only 22 out of 4,966 patients had appendiceal neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…A recent audit from the UK reported that more than 100 appendiceal specimens were not reviewed by surgeons, with no significant health or medico-legal implications after the operation [ 21 ]. A multicentric prospective analysis conducted in the Netherlands [ 16 ] involving 7,339 patients, included thorough inspection and palpation of the appendix and mesoappendix by surgeons. They found that 67.7% of the specimens would have been deemed unnecessary for histopathological examination, as only 22 out of 4,966 patients had appendiceal neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…Two systematic reviews published in 2011 and 2020 stated that it is impossible to conclude whether routine histopathology is justified but recommended that until more reliable data becomes available, histopathological examination of the removed appendix should continue to be carried out ( 20 , 21 ). However, Bastiaenen et al ( 24 ), in a multicenter, prospective, cross-sectional study with 7,339 patients submitted to appendectomy for suspected appendicitis, found robust evidence that selective histopathological examination of appendiceal specimens following the initial macroscopic evaluation by the surgeon was oncologically safe and could lead to significant cost savings. Our findings align with these conclusions, demonstrating significant limitations of the routine histopathological analysis, with a low agreement with the intraoperative severity classification, lack of association with post-operative outcomes, and low incidence of associated etiologies.…”
Section: Discussionmentioning
confidence: 99%